2019
DOI: 10.21814/unio.5.1.249
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of collaborative economy in the european union

Abstract: The paper distinguishes between sharing economy and collaborative economy, focusing on the legal framework of collaborative platforms (such as Uber or Airbnb) according to EU law. Case-law from the Court of Justice of the European Union (CJEU) and the position of the European Commission are analyzed in this regard. It is concluded that there is no harmonization, within the European Union, of the legal regime applicable to certain collaborative platforms. As such, specific regulation of collaborative platforms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Thus, it is concluded that there is a need in the European Union to harmonize the legal regime applicable to the business models of collaborative platforms. This conclusion aligns with Rodrigues's earlier findings [41]. Similarly, and generally, this study's findings are consistent with those of Echikson [6] and Tatarinov et al [42].…”
Section: Discussionsupporting
confidence: 94%
“…Thus, it is concluded that there is a need in the European Union to harmonize the legal regime applicable to the business models of collaborative platforms. This conclusion aligns with Rodrigues's earlier findings [41]. Similarly, and generally, this study's findings are consistent with those of Echikson [6] and Tatarinov et al [42].…”
Section: Discussionsupporting
confidence: 94%